2018
DOI: 10.1039/c8nr04081h
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature nanospectroscopy of the structural ferroelectric phases in single-crystalline barium titanate

Abstract: We optically investigate the local-scale ferroelectric domain structure of tetragonal, orthorhombic, and rhombohedral barium titanate (BTO) single crystals using scattering-type scanning near-field infrared (IR) optical microscopy (s-SNIM) at temperatures down to 150 K. Thanks to the precisely tunable narrow-band free-electron laser FELBE, we are able to explore the spectral fingerprints and IR resonances of these three phases and their domain orientations in the optical IR near-field. More clearly, every stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The first study of low‐temperature s‐SNOM was performed by Yang et al, and the study involved the s‐SNOM imaging of V 2 O 3 during the IMT at ≈200 K ( Figure a) . In the following year, Döring et al performed the s‐SNOM imaging of the barium titanate ferroelectric domain at ≈222 K (Figure b) . In 2016, McLeod et al set a milestone by systematically demonstrating the use of s‐SNOM to study SCQM and observed the IMT of V 2 O 3 at 160–180 K with high spatial resolution and SNR (Figure c) .…”
Section: Current Stagementioning
confidence: 99%
“…The first study of low‐temperature s‐SNOM was performed by Yang et al, and the study involved the s‐SNOM imaging of V 2 O 3 during the IMT at ≈200 K ( Figure a) . In the following year, Döring et al performed the s‐SNOM imaging of the barium titanate ferroelectric domain at ≈222 K (Figure b) . In 2016, McLeod et al set a milestone by systematically demonstrating the use of s‐SNOM to study SCQM and observed the IMT of V 2 O 3 at 160–180 K with high spatial resolution and SNR (Figure c) .…”
Section: Current Stagementioning
confidence: 99%
“…[12][13][14][15] Wavelength-independent spatial resolution in the order of ∼ 10 nm has been demonstrated via s-SNOM and nano-FTIR for different material systems, such as metal/nonmetal structures, [16][17][18][19] organic 16,20 and biological materials, 1,21,22 semiconductors, 18,23 and ferroelectric domain structures. [24][25][26][27] Close to material resonances such as plasmon and phonon modes, signal strength and material contrast in s-SNOM can be strongly enhanced. 17,[24][25][26][27][28][29][30][31] At infrared wavelengths, this mechanism is highly sensitive to the material properties and may be applied to polar materials, 28,31 metals, semiconductors, 18,23 and biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…13,[17][18][19][20][21][22] In addition to the spatial resolution, the probing depth of s-SNOM of about 100 nm 21,23-26 presents a major advantage for the investigation of small volumes or thin film samples, allowing for IR thin film spectroscopy with negligible direct substrate contribution to the optical signal. 27 The signal strength of s-SNOM is greatly enhanced via polaritoninduced resonant tip-sample interaction, 12,17,27,[30][31][32][34][35][36][37][38][39][40][41][42][43][44][45] which is of special advantage when exploring technically challenging wavelength regimes, 17,45 such as the "THz gap" (30-300 lm, i.e., 1-10 THz). 46 Particularly, sample-resonant s-SNOM provides enhanced sensitivity to the smallest material variations such as doping level and charge carrier concentration, 22,36,39,47 optical anisotropy tensor orientation in ferroelectric materials, 30,31,40,48 polymorphism, 36 and local stress distribution.…”
mentioning
confidence: 99%
“…The wavelength regions of interest are investigated with a homebuilt s-SNOM that implements demodulation at higher harmonics of the mechanical cantilever oscillation frequency 53,54 and a selfhomodyne detection scheme, with the latter leading to a combined response of near-field amplitude and phase. 17,53 For illumination, we use the tunable narrow-band free-electron laser (FEL) at the Helmholtz-Zentrum Dresden-Rossendorf (HZDR), Germany, 27,31,40,41,55 which is a linearly-polarized, pulsed laser source at 13 MHz repetition rate covering the wavelength range of 5-250 lm, i.e., 1.2-60.0 THz. 56 The experimental setup is described in detail elsewhere.…”
mentioning
confidence: 99%